Energetic Couplings in Ferroics. (8th October 2021) - Zhao, Hong Jian; Chen, Peng; Prosandeev, Sergey; Paillard, Charles; Patel, Kinnary; Íñiguez, Jorge; Bellaiche, Laurent
Abstract: Ferroics include diverse degrees of freedom (such as structural distortions and magnetic moments) among which cross couplings occur, rendering a large variety of interesting phenomena. Determining such couplings, based on symmetry analysis, is not only important to interpret observed phenomena but can also result in novel predictions to be then experimentally checked. Often, such energetic couplings are difficult to construct without a deep knowledge of group theoretical symmetry principles. In the present review, a crash course toward the derivation of energetic couplings, without using much group theoretical language, is provided. Rather, the present approach relies on a graphical technique and suitable symbolic language, which naturally yields some known couplings (resulting in, e.g., spin/dipole canting, magnetically driven polarization, and antipolar/antiferroelectric states). This review also reports and discusses other symmetry‐allowed energetic terms, including some leading to the occurrence of an electric polarization in a variety of materials, and "exotic" ones that generate complex phases and phenomena in, for example, nanostructures and heterostructures. Abstract : A crash course toward the derivation of energetic couplings, describing the electromagnetic phenomena in ferroics, is provided. In particular, a graphical technique and suitable symbolic language is developed in order to reproduce several known couplings such as spin/dipole canting, magnetically driven polarization, and antipolar/antiferroelectric states. Further, some other symmetry‐allowed energetic terms are also discussed.